2015
DOI: 10.3390/su71014309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Use and Slope Gradient on Soil Erosion in a Red Soil Hilly Watershed of Southern China

Abstract: Abstract:A study was undertaken to develop an appropriate plan of land use under suitable slope gradient to control soil erosion from a red soil hilly watershed of southern China by using the GeoWEPP (Geo-spatial Interface for the Water Erosion Prediction Project) model. The model was calibrated and validated using monitoring data of the outlet from 2010 to 2012, in which the 2010 and 2012 annual total runoff and sediment yield data were used for calibration, and the 2011 monthly runoff and sediment yield data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 39 publications
(39 reference statements)
1
41
0
1
Order By: Relevance
“…Obstajajo tudi seveda števil-ne druge enačbe za izračun stopnje erozije glede na naklon (npr. Chaplot & le Bissonnais, 2003;Assouline & Ben-Hur, 2006;Zhao et al, 2014;Zhang et al, 2015), ki pa upoštevajo še številne druge parametre, kot so intenziteta in trajanje padavin, usmerjenost brazd, natančen tip vegetacije in njena gostota, ki jih za dano območje ni bilo možno pridobiti ali izmeriti. Enačbe, ki določajo stopnjo erozije in ki so bile dobljene pri navedenih razikavah so posledično zelo specifične za testne lokacije, ki so jih raziskovalci uporabili za izračun sopnje erozije.…”
Section: Metodologijaunclassified
“…Obstajajo tudi seveda števil-ne druge enačbe za izračun stopnje erozije glede na naklon (npr. Chaplot & le Bissonnais, 2003;Assouline & Ben-Hur, 2006;Zhao et al, 2014;Zhang et al, 2015), ki pa upoštevajo še številne druge parametre, kot so intenziteta in trajanje padavin, usmerjenost brazd, natančen tip vegetacije in njena gostota, ki jih za dano območje ni bilo možno pridobiti ali izmeriti. Enačbe, ki določajo stopnjo erozije in ki so bile dobljene pri navedenih razikavah so posledično zelo specifične za testne lokacije, ki so jih raziskovalci uporabili za izračun sopnje erozije.…”
Section: Metodologijaunclassified
“…Only 0.0002796% and 0.0000042% were classified as severe and very severe potential risk respectively. Figure 11 below proves that the mean annual soil loss is proportional to the slope due to the effect of topographic factor as mentioned by Zhang et al (2015). When the slope is more than 140% the mean annual soil loss will reach the maximum mean annual soil loss (7.76 ton/ha.year), in contrast when the slope is very low (0-2%), the mean annual soil loss will be very low (0.08 ton/ha.year).…”
Section: Figure 9: Soil Loss Amountmentioning
confidence: 99%
“…A similar outcome has been reported by Saghafian et al [11] as they concluded that converting natural land use into other uses, particularly dry-farming, played the dominant factor in increasing the amount of sediment load within the Kasilian Watershed in Iran. In another study, the results of a GeoWEPPapplied experiment on a hilly watershed in southern China indicated that land use type changing from forest to agriculture caused sediment amount to increase by 42.6% [32]. Morover, in a research investigating how soil loss and sediment yields were affected by the land-use/land-cover scenarios using a GeoWEPP model, Maalim et al [14] found that the average annual sediment yields increased from 0.13 t/ha to 2.15 t/ha for current agricultural lands and pre-settlement land-use/land-cover, respectively, within the Le Sueur Watershed in Minnesota.…”
Section: Predicted Sediment Yields In the Godrahav Creek Watershedmentioning
confidence: 99%